E-COMMERCE PENJUALAN KOPI GAYO : Studi Kasus : UMKM Ine Kopi di Kecamatan Bandar, Aceh - Eko Siswanto; Mahmuda Saputra; Hendry Syahputra (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2022)
E-Commerce is a flexible buying and selling system where a buyer does not need to come to a physical store to buy an item. Currently e-commerce is one of the alternative options for a business that is especially engaged in the field of processed coffee as a medium of information that facilitates interaction between sellers and buyers without limited space and time